PENGGUNAAN KAPUR DOLOMIT [CAMG(CO3)2] PADA DASAR KOLAM TANAH SULFAT MASAM TERHADAP PERBAIKAN KUALITAS AIR PADA PEMELIHARAAN BENIH IKAN PATIN (Pangasius sp.) - Zainal Umari; Marsi .; Dade Jubaedah (Universitas Sriwijaya, 2017)
ABSTRACTAcidic waters was common problem in aquaculture in acidic soil area. Poor water quality in the acid sulfate soil pond has potential to decrease fish survival rate dan fish growth. Liming pond is one of method to neutralize (buffer) acid in fish pond. The aim of the research is to determine the best dosage of dolomite lime [CaMg(CO3)2] in acid sulfate soil pond to water quality, survival rate and growth of catfish. The research conducted on September-October 2016 in Laboratorium Kolam Percobaan, Program Studi Budidaya Perairan, Fakultas Pertanian, Universitas Sriwijaya, Indralaya. The research based on completely random design with four treatments and three replications. The treatments were different dosage of dolomite lime that are 6 (P1), 9 (P2), 12 (P3), and 15 (P4) ton/ha equivalent CaCO3. The research parameter were water quality, survival rate, and growth. The result showed that dosage 12 ton/ha was the best treatment that has highest survival rate 96.6 %, absolute growth of length 3.5 cm, weight 7.91g and feed efficiency 106,77%. Keywords: liming, dolomite, acid sulfate soil, seedling catfish